A prototype MR insertable brain PET using tileable GAPD arrays. Issue 4 (13th March 2013) - Hong, Key Jo; Choi, Yong; Jung, Jin Ho; Kang, Jihoon; Hu, Wei; Lim, Hyun Keong; Huh, Yoonsuk; Kim, Sangsu; Jung, Ji Woong; Kim, Kyu Bom; Song, Myung Sung; Park, Hyun‐wook
Abstract : Purpose: : The aim of this study was to develop a prototype magnetic resonance (MR)‐compatible positron emission tomography (PET) that can be inserted into a MR imager and that allows simultaneous PET and MR imaging of the human brain. This paper reports the initial results of the authors' prototype brain PET system operating within a 3‐T magnetic resonance imaging (MRI) system using newly developed Geiger‐mode avalanche photodiode (GAPD)‐based PET detectors, long flexible flat cables, position decoder circuit with high multiplexing ratio, and digital signal processing with field programmable gate array‐based analog to digital converter boards. Methods: : A brain PET with 72 detector modules arranged in a ring was constructed and mounted in a 3‐T MRI. Each PET module was composed of cerium‐doped lutetium yttrium orthosilicate (LYSO) crystals coupled to a tileable GAPD. The GAPD output charge signals were transferred to preamplifiers using 3 m long flat cables. The LYSO and GAPD were located inside the MR bore and all electronics were positioned outside the MR bore. The PET detector performance was investigated both outside and inside the MRI, and MR image quality was evaluated with and without the PET system. Results: : The performance of the PET detector when operated inside the MRI during MR image acquisition showed no significant change in energy resolution and count rates, except for a slight degradation in timing resolution with an increase from 4.2 to 4.6 ns. Simultaneous PET/MR images of a hot‐rod and Hoffman brain phantom were acquired in a 3‐T MRI. Rods down to a diameter of 3.5 mm were resolved in the hot‐rod PET image. The activity distribution patterns between the white and gray matter in the Hoffman brain phantom were well imaged. The hot‐rod and Hoffman brain phantoms on the simultaneously acquired MR images obtained with standard sequences were observed without any noticeable artifacts, although MR image quality requires some improvement. Conclusions: : These results demonstrate that the simultaneous acquisition of PET and MR images is feasible using the MR insertable PET developed in this study.